Gastropleural Fistula as a Rare Complication of Gastric Sleeve Surgery: A Case Report and Comprehensive Literature Review - Fahad Alghanim; Ali Alkhaibary; Abdulmohsen Alzakari; Abdullah AlRumaih (Case Reports in Surgery)
Gastropleural fistula (GPF) is a rare, life-threatening complication of gastric sleeve surgery. GPF is an uncommon differential diagnosis to consider in a patient presenting with a picture of pneumonia. As such, GPF should be suspected in a patient with a history of nonresolving pneumonia who recently underwent gastric sleeve surgery. To the best of our knowledge, only eight cases of gastropleural fistulas after bariatric surgery have been reported in the literature. Herein, we report a case of gastropleural fistula after gastric sleeve surgery and review the pertinent literature. A gastropleural fistula is an exceedingly rare and life-threatening complication postbariatric surgery. Nonsurgical conservative management (total parenteral nutrition, percutaneous drainage, and antibiotics with endoscopic stenting) can be considered.